Optimizing Tomato (Solanum lycopersicum L.) Growth With Different Combinations of Organo-Mineral Fertilizers - Traoré, Adama; Bandaogo, Alimata Arzouma; Savadogo, Ouango Maurice; Saba, Fatimata; Ouédraogo, Audrey Leiticia; Sako, Yaya; Sermé, Idriss; Ouédraogo, Souleymane (Frontiers in Sustainable Food Systems, 2022)
With the aim of promoting sustainable agriculture that respects the environment and human health, a study was carried out to evaluate the impact of organic and mineral fertilizers on tomato plant cultivation. The study was carried out at the Research Station of Farako-Bâ in Burkina Faso. A complete randomized block of Fisher design with four replications was used to carry out the experiment. The treatments were as follows: T0: control (compost 15 t/ha); T1: compost (15 t/ha) + biosol (160 kg/ha) + urea (35 kg/ha) + NPK (87.5 kg/ha) + KCl (52.5 kg/ha); T2: compost (15 t/ha) + neem seed cake (10 t/ha) + urea (100 kg/ha) + NPK (250 kg/ha) + KCl (150 kg/ha); T3: compost (15 t/ha) + biochar (10 t/ha) + urea (100 kg/ha) + NPK (250 kg/ha) + KCl (150 kg/ha). The data collected were collar diameter, height of plants, number of fruits, fruit diameter, and tomato fruit yield. The results showed that the combination organo-mineral fertilizers had a significant effect on tomato plant productivity. Application of neem seed cake and mineral fertilizers was the most efficient treatment with a yield increase of 53% and 40% in 2019, respectively. In 2020, the yield increase was 32 and 85% for biochar and biosol, respectively. Incorporation of organo-mineral fertilizers has improved soil organic and nutrient status, which ultimately promotes crop growth of tomato plant. Neem cake can be effectively used to increase tomato plant productivity and farmer's income and also maintain soil fertility.